Tensile behavior of an eutectic Pb–Sn alloy processed by ECAP and rolling - Livia Ponzo Lugon (Journal of Materials Research and Technology, 2014)
A eutectic lead–tin alloy was prepared by melting the commercially pure metals and cast in cylindrical molds with 10 mm diameter. The billets were processed by 4 passes of ECAP using a die with 90° between channels through route A and rolled to a final thickness of ∼1 mm. The microstructure was determined by optical microscopy. Tensile tests were carried out at room temperature in the strain rate range between 10−4 and 10−2 s−1. The results show the elongation to failure increases at low strain-rates. The strain-rate sensitivity parameter was determined and a maximum value of ∼0.4 was observed at the lowest strain-rate.